Diplacodes lefebvrii in Sardinia, a new species for the Italian fauna (Odonata: Libellulidae) - Rattu, Andrea; Leo, Piero; Moratin, Raynald; Hardersen Sönke (Fragmenta entomologica, 2014)
Diplacodes lefebvrii (Rambur, 1842) is a libellulid dragonfly, which is common and widespread in Africa and across the Indian Ocean. While this species is fairly common in the south and east of the Mediterranean, its European range is confined to Cyprus, the island of Rhodes and the south of the Iberian Peninsula. Here we report the first record of D. lefebvrii for Italy, which was captured near Cagliari (Sardinia) on 11.IX.2013. In October 2014, a population of the same species was observed at a small wetland on the island “Isola di San Pietro” (Sardinia). Here the observed sex ratio of D. lefebvrii was strongly biased in favour of females and only a single male was observed.